2014
DOI: 10.1016/j.combustflame.2013.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Combustion chemistry and flame structure of furan group biofuels using molecular-beam mass spectrometry and gas chromatography – Part I: Furan

Abstract: Fuels of the furan family, i.e. furan itself, 2-methylfuran (MF), and 2,5-dimethylfuran (DMF) are being proposed as alternatives to hydrocarbon fuels and are potentially accessible from cellulosic biomass. While some experiments and modeling results are becoming available for each of these fuels, a comprehensive experimental and modeling analysis of the three fuels under the same conditions, simulated using the same chemical reaction model, has -to the best of our knowledge -not been attempted before. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
157
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 120 publications
(178 citation statements)
references
References 47 publications
16
157
1
4
Order By: Relevance
“…Selected results from the only comparative suite of flame studies of the three furans reported in Refs. [173,177,178] are presented in Figure 10. Here,m ole fractions for these onedimensional low-pressure flames are reported as afunction of the reaction progress,g iven in terms of height above the burner.…”
Section: Validation Examples For Furanic Fuels:speciation Reaction Pmentioning
confidence: 99%
See 3 more Smart Citations
“…Selected results from the only comparative suite of flame studies of the three furans reported in Refs. [173,177,178] are presented in Figure 10. Here,m ole fractions for these onedimensional low-pressure flames are reported as afunction of the reaction progress,g iven in terms of height above the burner.…”
Section: Validation Examples For Furanic Fuels:speciation Reaction Pmentioning
confidence: 99%
“…[163] This knowledge has led to the formulation of reaction classes and associated rate rules for alcohols,a ldehydes,a nd carbonylic species, which permit the further development of mechanisms for such compounds. [167,168] Quite recently,c hemical mechanisms have also been developed for fuels from second-generation processes and beyond, including larger alcohols, [164,165] ethers, [169] and ketones, [170,171] and as ubstantial amount of work has been devoted to the furans [172][173][174][175][176][177][178] and tetrahydrofurans,w hich are in the focus of the present Review. [69,179,180] It is interesting to understand how macroscopic properties such as derived cetane numbers (compare Section 2a nd Figure 1) for advanced biofuels relate to the chemical kinetics mechanisms,s ince such understanding can substantially support strategies for fuel design.…”
Section: Mechanism Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…There were amount of literatures focusing on the study of chemistry and flame structure of furanic fuel flames. Using molecular beam mass spectrometry and gas chromatography, the combustion chemistry and flame structure of furan group biofuels in flames of furanic compounds and those of other fuels have been investigated by Kohse-Höinghaus's group [39,40]. They found that DMF offered a priori surprising ability to form soot precursors compared to less substituted furans and to other fuels [41,42].…”
Section: Introductionmentioning
confidence: 99%